FDIC-sponsored self-insured depositors: using insurance to gain market discipline and lower the cost of bank funding - Panos Konstas (Levy Economics Institute of Bard College, 2005)
Insured depositors have no reason to care how their banks perform or how safe they are. Only uninsured depositors have that incentive. This paper offers a plan to replace some insured deposits with uninsured deposits. The plan: the FDIC would guarantee loan contracts if the loan takers deposited the proceeds exclusively in uninsured deposits and backed those deposits with equity. This would ensure that the loan takers could share the likely costs if any of their depositories failed. The loans made under FDIC guarantee would only require interest at the risk-free rate. Thus the loan takers could offer the proceeds at lower rates than the rates paid on current deposits. Accordingly, funding by banks would shift to the new deposits, and since the new self-insured depositors would have equity at stake, they would have no choice but to duly monitor their banks and impose rate premiums based on each bank's indigenous risk. With these reforms, some very costly imperfections of current deposit insurance would be eliminated: the FDIC would now have in place a program that would dissuade banks from moral hazard and high risk and set the foundation for better disciplined, safer, and more cost-efficient banking.
Keywords: G21; G22; G28; 330; Reforming FDIC insurance; moral hazard; market discipline; bank risk pricing; cost of funds to banks